Development and testing of the Educators' Professional Development scale (EduProDe) for the assessment of social and health care educators' continuing professional development. (March 2021) - Koskimäki, Minna; Mikkonen, Kristina; Kääriäinen, Maria; Lähteenmäki, Marja-Leena; Kaunonen, Marja; Salminen, Leena; Koivula, Meeri
Abstract: Background: Social and health care educators are crucial to educating competent professionals that are prepared to work in a rapidly changing society. Previous studies have primarily assessed educators' continuing professional development from a single perspective. It would be important to gauge educators' perceptions about their professional development from multiple dimensions to identify the strengths and weaknesses of the current learning process. Aim: To develop and validate a new educators' professional development scale that is relevant to social and health care education institutions. Method: The development and validation of the scale comprised four phases: defining continuing professional development; creating an item pool; an expert review of the item pool; and psychometric testing of the scale. Face and content validity were evaluated by two expert panels. The initial item pool included 104 items, with 41 remaining after the expert review. A total of 2330 social and health care educators from 29 organizations were invited to respond to the developed self-assessment survey. The response rate was 18% (n = 422). Results: Explorative factor analysis identified six factors, including a total of 22 items, that accounted for 68.37% of the total variance. The factors defined different elements of continuing professional development for educators, namely, "need for pedagogical development" (7 items), "need to manage challenging situations in teaching" (3 items), "leadership of competence development" (3 items), "self-directed learning" (3 items), "need to develop clinical competence" (3 items) and "benefits of professional development" (3 items). Internal consistency for the six subscales, measured through Cronbach's alpha coefficient, ranged from 0.70 to 0.89. Conclusion: The EduProDe scale is a relevant and reliable tool for the planning and evaluation of continuing professional development processes or programs designed for educators of social and health care students. Highlights: The EduProDe scale provides a multi-faceted view of continuing education. The scale is reliable as it has a Cronbach's alpha value of 0.89. The Cronbach's alpha values of the six subscales range from 0.70 to 0.89 Organizations can use the scale to assess current continuing education programs.